Atypical primary melanoma of the umbilicus: A case report - Vulović Dejan; Kozarski Jefta; Petrović Dušica; Gregović Miljan; Jovanović Dalibor; Vulović Dejana; Radivojčević Uroš (Vojnosanitetski Pregled)
Introduction. The umbilicus (omphalos; the navel; belly button; tummy button) is important in a medical and psychosocial context. Umbilical tumors are rare and can be benign or malignant, primary or secondary. The most common are malignant metastatic tumors, especially The Sister Mary Joseph Nodule, an eponym for the umbilical metastasis of intra-abdominal malignant tumors. Primary melanoma of the umbilicus is very rare, there is few literature data about it and its incidence is not well known. Therefore, the aim of this study was to present a patient with a rare localization of the primary skin melanoma, that was, also, of atypical form, large and involved the whole umbilicus and surrounding skin. Case Report. In this report, the patient had nodular red tumor which involved the whole umbilicus. Tumor had rapid growth. In the differential diagnosis, the tumor most by resembled a pyogenic granuloma. After the surgery, the histopathological finding showed the primary nodular skin melanoma (Clark V, Breslow 10 mm, positive for: vimentim S – 100 protein, melan – A and HMB – 45, and negative for EMA, with moderately high proliferative activity). Conclussion. According to literature data, this is 27th case of the primary melanoma of the umbilicus since 1916 when it was first reported. By presenting this rare clinical case, we emphasize that any skin lesion that is removed, must be sent to a histopathologic analysis.